A new record and mitochondrial identification of Synidotea laticauda Benedict, 1897 (Crustacea: Isopoda: Valvifera: Idoteidae) from the Yangtze Estuary, China - Liu, Wenliang; Liang, Xiaoli; Zhu, Xiaojing (Zootaxa, 2017)
Synidotea laticauda Benedict, 1897 is recorded for the first time from China. Previous records of Synidotea laevidorsalis (Miers, 1881) from the Yangtze Estuary are misidentifications of this species. Molecular comparison using the mitochondrial sequence COI shows that S. laticauda from the Yangtze Estuary is identical to a NCBI sequence of S. laevidorsalis from Korea, probably misidentified. The origin of this widespread introduced species is discussed.